The Influence of Early Maladaptive Schemas on the Causal Links between Perceived Injustice, Negative Affect, and Aggression. Issue 2 (3rd April 2021) - Van Wijk-Herbrink, Marjolein F.; Lobbestael, Jill; Bernstein, David P.; Broers, Nick J.; Roelofs, Jeffrey; Arntz, Arnoud
Abstract: This study adds to the understanding of why some adolescent boys react to unfair situations with anger and aggression, whereas others do not. We used an experimental design to test whether early maladaptive schemas influence the causal links between perceived injustice, negative affect, and aggression. Thirty-seven adolescent boys (13–18 years old; participation rate 67%) with severe behavior problems were randomly assigned to either the experimental condition, where a feeling of unfairness was induced, or to the control condition. Results showed that the effects of perceived injustice on aggression were mediated by angry feelings, and that this mechanism was conditional on levels of Abandonment and Entitlement schemas. These results suggest that even vulnerable schemas may underlie aggression, and that aggression treatment may benefit from a focus on underlying maladaptive schemas.